Clinical utility of genetic testing in early-onset kidney disease: seven genes are the main players. Issue 4 (3rd February 2021) - Domingo-Gallego, Andrea; Pybus, Marc; Bullich, Gemma; Furlano, Mónica; Ejarque-Vila, Laia; Lorente-Grandoso, Laura; Ruiz, Patricia; Fraga, Gloria; López González, Mercedes; Piñero-Fernández, Juan Alberto; Rodríguez-Peña, Lidia; Llano-Rivas, Isabel; et al.
Abstract: Background: Inherited kidney diseases are one of the leading causes of chronic kidney disease (CKD) that manifests before the age of 30 years. Precise clinical diagnosis of early-onset CKD is complicated due to the high phenotypic overlap, but genetic testing is a powerful diagnostic tool. We aimed to develop a genetic testing strategy to maximize the diagnostic yield for patients presenting with early-onset CKD and to determine the prevalence of the main causative genes. Methods: We performed genetic testing of 460 patients with early-onset CKD of suspected monogenic cause using next-generation sequencing of a custom-designed kidney disease gene panel in addition to targeted screening for c.428dupC MUC1 . Results: We achieved a global diagnostic yield of 65% (300/460), which varied depending on the clinical diagnostic group: 77% in cystic kidney diseases, 76% in tubulopathies, 67% in autosomal dominant tubulointerstitial kidney disease, 61% in glomerulopathies and 38% in congenital anomalies of the kidney and urinary tract. Among the 300 genetically diagnosed patients, the clinical diagnosis was confirmed in 77%, a specific diagnosis within a clinical diagnostic group was identified in 15%, and 7% of cases were reclassified. Of the 64 causative genes identified in our cohort, 7 ( COL4A3, COL4A4, COL4A5, HNF1B, PKD1, PKD2 and PKHD1 ) accounted for 66% (198/300) of the genetically diagnosed patients. Conclusions: Two-thirds of patients with early-onset CKD in this cohort had a genetic cause. Just seven genes were responsible for the majority of diagnoses. Establishing a genetic diagnosis is crucial to define the precise aetiology of CKD, which allows accurate genetic counselling and improved patient management.